Bandits, Patriots or Delinquents? Social Protest in Rural Cuba (1878–1902). (1st April 2015) - ,
Abstract : A charismatic form of banditry has been broadly interpreted as the only manifestation of rural protest in nineteenth-century Cuba, a version of history encouraged by the Spanish authorities who criminalised protest demonstrations in the countryside to justify repression against supporters of independence and the rural population in general. But there were also other forms of protest that were more 'silent' and less visible but equally effective. By analysing the socioeconomic changes and the expressions of social unrest, as well as their methods and motivations, this article examines the different ways farmers and labourers reacted against oppression in the period from 1878 after the end of the first war of independence, to 1902 when the first Cuban Republic was established.